2019
DOI: 10.1002/lt.25598
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip Strength Adds More Prognostic Value to the Model for End‐Stage Liver Disease Score Than Imaging‐Based Measures of Muscle Mass in Men With Cirrhosis

Abstract: Sarcopenia is associated with mortality in cirrhosis, but there is no gold standard for its diagnosis. The comparative utility of different diagnostic methods is unknown. This single‐center observational cohort study followed 145 men referred for liver transplant evaluation between 2005 and 2012. Muscle mass was estimated by handgrip strength, dual energy X‐ray absorptiometry (DEXA) lean mass, and single‐slice computed tomography (CT) scan at the fourth lumbar vertebra. Recorded outcomes included time to death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 29 publications
3
67
0
Order By: Relevance
“…In this study, however, muscle mass was assessed using dual energy x-ray absorptiometry (DEXA), which might also be a reason for the discrepant results compared to liver cirrhosis [23]. Large differences in the prevalence of sarcopenia between CT scan (70.3%) and DEXA (38.7%) were also found in patients with chronic liver disease [24]. In chronic obstructive pulmonary disease, the prevalence of sarcopenia was not different between the two definitions (16.8% vs. 13.1%).…”
Section: Discussionmentioning
confidence: 85%
“…In this study, however, muscle mass was assessed using dual energy x-ray absorptiometry (DEXA), which might also be a reason for the discrepant results compared to liver cirrhosis [23]. Large differences in the prevalence of sarcopenia between CT scan (70.3%) and DEXA (38.7%) were also found in patients with chronic liver disease [24]. In chronic obstructive pulmonary disease, the prevalence of sarcopenia was not different between the two definitions (16.8% vs. 13.1%).…”
Section: Discussionmentioning
confidence: 85%
“…Contrary to the CST, the prognosis value of HGS has been demonstrated in many works in patients with cirrhosis. HGS is an independent factor of mortality [33,34], but weakly correlates with muscle mass and quality assessed on cross-sectional imaging [35]. These results imply that the complementarity of a quantification with a functional approach is needed.…”
Section: How To Correctly Assess Muscle Function and Mass In Patientsmentioning
confidence: 94%
“…Sinclair et al recently found a large difference in the prevalence of sarcopenia between CT (Computed Tomography) scan (70.3%) and DEXA (38.7%). DEXA underestimates the prevalence of sarcopenia in patients with fluid overload and cannot be used in patients with CLD [33].…”
Section: Which Tools Do Not Work In Chronic Liver Diseases?mentioning
confidence: 99%
See 1 more Smart Citation
“…We read the article by Sinclair et al (1) with great interest, and we sincerely congratulate them for highlighting the importance of sarcopenia in patients with cirrhosis. Notably, they wanted to show the prognostic value of different parameters related to sarcopenia.…”
Section: To the Editormentioning
confidence: 97%